Effect of ultraviolet irradiation on poly(3, 4-ethylenedioxythiophene) doped with ClO4 thin films using electropolymerization. (10th May 2017) - Takahashi, Momoko; Deguchi, Toshiaki; Takashiri, Masayuki
Abstract: Effects of ultraviolet (UV) irradiation on ClO4 doped poly(3, 4-ethylenedioxythiophene) (PEDOT) thin films were investigated in terms of the structural and thermoelectric properties. The ClO4 doped PEDOT films were synthesized by electropolymerization; subsequently, these films were exposed to UV light for predetermined time intervals in ambient air. UV irradiation led to an agglomeration of PEDOT domains, which in turn causes an increase in the grain size and the surface roughness, as observed in scanning electron microscopy images. Fourier transform infrared spectroscopy revealed that the molecular structure of PEDOT was not affected by UV irradiation. Electron spin resonance (ESR) analysis revealed that the spin density was drastically reduced by short-term UV irradiation of less than 5 min. Upon increasing the UV irradiation time, the spin density gradually increased. A similar relationship was observed between the UV irradiation time and the electrical conductivity. Further, short-term UV irradiation also increased the power factor. The maximum power factor was found to be 1.9 µW/(m·K 2 ) at a UV irradiation time of 2.5 min, this is approximately 60% higher than that of the pristine PEDOT thin film. Therefore, we conclude that the appropriate UV irradiation dosage enhances the thermoelectric performance, but an excess UV irradiation leads to a deterioration of the same.